Highly Conformationally Restricted Cyclopropane Tethers with Three‐Dimensional Structural Diversity Drastically Enhance the Cell Permeability of Cyclic Peptides. Issue 13 (10th January 2017) - Matsui, Kouhei; Kido, Yasuto; Watari, Ryosuke; Kashima, Yousuke; Yoshida, Yutaka; Shuto, Satoshi
Abstract: Invited for the cover of this issue is the group of Kouhei Matsui and Satoshi Shuto at Shionogi & Co., Ltd. and at Hokkaido University. The image depicts the cyclopropane tethers with three‐dimensional structural diversity that are able to remarkably change the conformation and physicochemical properties of cyclic peptides due to the characteristic steric feature of cyclopropane. Read the full text of the article at 10.1002/chem.201604946 . Abstract : " This study demonstrates that by introducing highly constrained cyclopropane tethers, cell‐membrane‐permeable cyclic peptides, which are conformationally dependent, can be obtained ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 3034 ff. (DOI:10.1002/chem.201604946 ).